Peryferyjna obecność. Problem recepcji literatury staroserbskiej w Polsce - Lis-Wielgosz, Izabela (Przekłady Literatur Słowiańskich, 2020)
In the article, a problem of translation of the old Serbian literary texts into Polish is discussed together with the basic mechanisms of the reception process of creativity revealed by the Orthodox Slavs from the Balkan region, that is, in other words, the works arisen in the circle of the Slaviae Orthodoxae and their presence in the Polish culture’s space which belonged to the circle of the Slaviae Latinae. The considerations regard the essence and function of translation, presence and absence of translated literature — its initial version in the target space, and their foundation is located in the collections of translations existing in the Polish reading circuit. The issue of the presence or position of the old South Slavonic literatures, namely, the old Serbian texts in their Polish translation, is featured in several possible perspectives. The problem is exposed in the aspect of these texts’ peripheral character and literary genetics.